Experimental Investigations on Performance and Emissions of Spark Ignition Engine - Krishna, M. V. S. Murali; Priyadarshni, Ch. Indira; Mohanthi, Ipsita; Sridevi, K. N. V. (Technological Innovation in Engineering Research Vol. 4, 2022)
Aim: Exhaust emissions from Internal Combustion Engines cause severe health hazards apart from causing environmental disorders. Investigations were carried out to evaluate the performance of variable speed, variable compression ratio, four- stroke, single cylinder, spark ignition (SI)engine having copper coated engine [CCE, copper-(thickness, 300 \(\mu\)m) coated on piston crown and inner side of cylinder head] provided with catalytic converter with sponge iron as catalyst with different test fuels of neat gasoline, gasohol (80% gasoline and 20% ethanol by volume) and methanol blended gasoline (80% gasoline and 20% methanol by volume) and compared with conventional engine (CE) with neat gasoline operation. Study Design: Performance parameters of speed, compression ratio, brake thermal efficiency (BTE), exhaust gas temperature (EGT) were varied with different values of brake mean effective pressure (BMEP). Methodology: The exhaust emissions of carbon monoxide (CO) and un-burnt hydro carbons (UBHC) were measured with different values of BMEP. The engine was provided with catalytic converter with sponge iron and manganese ore as catalysts. There was provision for injection of air into the catalytic converter. The performance of the catalyst was compared with one over the other. Brief Results: Brake thermal efficiency increased with gasohol with both versions of the engine. CCE showed improvement in the performance when compared with CE with both test fuels. Brake thermal efficiency increased with compression ratio and marginally with speed of the engine. Methanol blended gasoline decreased exhaust emissions effectively in comparison with gasohol with both versions of the engine. Catalytic converter with air injection significantly reduced pollutants with different test fuels on both configurations of the engine.